2016
DOI: 10.1111/trf.13721
|View full text |Cite
|
Sign up to set email alerts
|

Use of intravenous immunoglobulin in neonates at a tertiary academic hospital: a retrospective 11‐year study

Abstract: This novel assessment of IVIG use in the NICU revealed the spectrum of disease for which IVIG is ordered. This study also found that key diagnostic tests needed to confirm an immune etiology for idiopathic jaundice are not performed routinely before IVIG receipt. Neonatal transfusion-related databases are needed to carry out pragmatic clinical trials to establish better evidence-based guidelines for IVIG therapy in the NICU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
0
6
0
1
Order By: Relevance
“…In a study done by Liberman et al, 37 neonates received IVIG over a 11-year period from 2003 to 2013 in a Canadian Tertiary care hospital which has on an average 4200 deliveries per year giving it a usage rate of around 0.08%. 5 The non-availability during yester years, the relatively high cost and the timely availability in current period, treating team decision are factors that would have influenced IVIG use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study done by Liberman et al, 37 neonates received IVIG over a 11-year period from 2003 to 2013 in a Canadian Tertiary care hospital which has on an average 4200 deliveries per year giving it a usage rate of around 0.08%. 5 The non-availability during yester years, the relatively high cost and the timely availability in current period, treating team decision are factors that would have influenced IVIG use.…”
Section: Discussionmentioning
confidence: 99%
“…3 It was also reiterated by the Cochrane review in 2015 by Ohlsson A et al, In coherence with increased availability of IVIG world-over, an increased usage in neonates is being noted, though its utilisation has not been investigated or audited thoroughly. 4,5 This study was planned to put light of IVIG usage in our hospital in the intramural neonatal unit. The objective of this study was to describe the usage pattern and indications for IVIG and its outcome in a state-run tertiary care NICU.…”
Section: Introductionmentioning
confidence: 99%
“…The 2004 AAP guidelines state that if the maternal blood group is O (+), it is an option to test the cord blood for the infant's blood type and to perform a DAT, but it is not required to do so provided there is appropriate surveillance [2]. Recent studies by our group and others support eliminating routine blood typing and DAT measurement in neonates born to blood group O (+) mothers [5][6][7][8]. We found that neonates who were blood group A or B and born to mothers of group O (+) (and thus were at some risk for ABO hemolytic disease) did not have a higher incidence of severe neonatal hyperbilirubinemia than did neonates of blood group O who were born to group O (+) mothers (and thus were at no risk for ABO hemolytic disease).…”
Section: Eliminating Routine Blood Typing and Dat Testing For Neonatementioning
confidence: 99%
“…In some nurseries, serum bilirubin is used to screen for hyperbilirubinemia and in others transcutaneous bilirubin (TcB) is used [4]. Some hospitals routinely perform blood typing and direct antiglobulin testing (DAT) on all neonates born to women of blood group O [5][6][7][8]. Recently, a series of publications exposed possible adverse effects of well-baby phototherapy and challenged the perception that neonatal phototherapy is totally benign [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Despite IVIG is thought to reduce the rate of hemolysis and consequently the need for exchange transfusions in theory, the conclusions of the previous research on the use of IVIG in ABO HDN are controversial in recent years [ 5 ]. Furthermore, as a kind of blood product, the use of IVIG has been associated with significant morbidity in neonates [ 6 , 7 ]. Therefore, additional clinical research evaluating IVIG in ABO HDN need to be performed before definitive conclusions can be drawn.…”
Section: Introductionmentioning
confidence: 99%